Relationship between gray directors and executive compensation in Indian firms - Krishna Prasad; K. Sankaran; Nandan Prabhu (European Journal of Management and Business Economics (EJM&BE), 2019)
Purpose The purpose of this paper is to examine the empirical relationship between gray directors (non-executive non-independent directors) and executive compensation among companies listed in India's National Stock Exchange (NSE). The paper also examines the possible interplay of relationships between controlling shareholder duality (controlling shareholder being the CEO), ownership category and executive compensation. Design/methodology/approach A sample of 438 firms listed in the NSE of India was studied using data spanning five financial years, 2012-2013 to 2016-2017. Findings Empirical evidence suggests that there is a positive association between the proportion of gray directors on the board and executive compensation. The sensitivity of executive compensation to gray directors is found to be higher among family controlled firms. This research has also found that CEOs who belong to controlling shareholder groups received higher pay than professional CEOs. The authors conjecture that these results suggest cronyism and may contribute to lower levels of corporate governance practices in the country. Research limitations/implications The hybrid board structure, which India has adopted with the desire to bring the best of Anglo Saxon and Japanese board philosophies, has paradoxically led to self-serving boards. Exploration of alternative thinking to bring about changes in the regulatory framework is, therefore, necessary. Originality/value Serious problems are identified with the philosophy behind board composition mandated by Listing Requirements for Indian firms with empirical evidence showing how the existing rules generate cronyism and unfairness to minority shareholders.
Keywords: 650; CEO pay; Controlling shareholder duality; Gray directors; Non-executive non-independent directors